Evaluation of the Quality of Commercial Control Materials and Homemade Lyophilized on Clinical Chemistry Parameters with the Sigma Metric Method - Maulida Azmi Wimasni Inah; Masdiva Putri Hidayah; Anik Handayati; Museyaroh; Lully Hanni Endarini; Edy Haryanto (Jurnal Teknokes, 2025)
Control materials are used to maintain the accuracy of testing procedures and the quality of laboratory results. However, commercial control materials are often considered less economical, so an alternative is needed, namely lyophilized human serum. Sigma metric helps improve laboratory operational costs efficiency through control settings and Westgard rule recommendations involving the Total Error Allowable (TEa) value, bias value (d%), and coefficient of variation (CV%). This study aims to determine the quality of commercial control materials and homemade lyophilized materials for blood glucose, uric acid, total cholesterol, and triglyceride parameters based on sigma values. This study used a comparative cross-sectional design. The samples included commercial control materials from one of the primary-level laboratories in Bangkalan District and homemade lyophilized samples from human serum collections. Data Analysis was conducted by statistically comparing the bias value and descriptively comparing the sigma value of commercial control material and homemade lyophilized. The results showed no significant difference in bias value between commercial control material and homemade lyophilized material for all parameters (significance value > α 0,05). The sigma values of commercial control material for blood glucose, uric acid, total cholesterol, and triglyceride parameters were 2.81 (poor), 2.41 (poor), 3.10 (marginal), and 2.14 (poor). The sigma values of the homemade lyophilized were 2.12 (poor), 1.76 (unacceptable), 3.36 (marginal), and 2.08 (poor). Based on the sigma values, the homemade lyophilized material was better for total cholesterol parameters, while the commercial control material was better for blood glucose, uric acid, and triglyceride parameters. It can be concluded that homemade lyophilized can be used as an alternative to commercial control materials, especially for total cholesterol parameters. These findings support the cost efficiency of laboratory operations through the development of more economical homemade lyophilized products that are suitable for use in laboratories.